Ulama in Indonesian Politics: Analysis on the Attitudes of The Majelis Ulama Indonesia (MUI) on the General Elections - Muhammad Asad (Universitas Islam Lamongan, 2022)
This article discusses the attitudes of Majelis Ulama Indonesia (MUI) on Indonesian general elections. It will compare the attitudes of the MUI in the general elections in the New Order and post-New Order era. There are six elections that are to be examined in this article, from 1977 to 2009. This article is based on qualitative research by using a comparative approach, specifically when searching for the difference in the attitude of the MUI in the New Order era and the MUI post-New Order. The data of this research is taken from the official magazine of MUI, Mimbar Ulama from the time it was published in 1975 to 2009. This article argues that the MUI in post-New Order times tried to be a player in the political context while in the New Order era the MUI took a safer stance. Under the New Order regime, the MUI could be regarded as playing safely by supporting the government. This standing is different from the post-New Order period where the MUI attitudes in the general elections are determined by political developments. The MUI changed its attitude both by distancing itself